Immigrants in Spain: skills acquisition and development. A regional study - Ignacio Díaz-Emparanza; Alexandra M. Espinosa (European Regional Science Association (ERSA), 2002)
The consequences of international migration for development in countries of origin and destination remain hotly debated. The immigration flows could be considered an appropriate mechanism to contribute to the development of origin countries if they recognize the qualifications of immigrants or contribute to the acquisition of skills. Correspondence analysis is used to determine the relation between education level, job position and legal situation of immigrants in Spain. The results indicate that immigrants are occupying non skilled tasks, even in the case of well educated immigrants. Furthermore, these immigrants have no options to increase their skills nor by experience (in the job) neither by theirself (attending a school), since the immigration police only authorizes very short migration. Then, Spain is not contributing appropriately to the development of origin countries.
Keywords: 330